Evaluation of fracture toughness and residual stress in AISI 316L electron beam welds. Issue 8 (12th April 2021) - Mokhtarishirazabad, Mehdi; Simpson, Chris; Kabra, Saurabh; Horne, Graeme; Palmer, Iain; Moffat, Andrew; Truman, Christopher; Knowles, David; Mostafavi, Mahmoud
Abstract: Weld residual stress and fracture behavior of 316L electron beam weldments, which are of particular interest in power generation industry, were investigated in this work. Two butt‐weld joints were manufactured in stainless steel 316L plates of 6 mm and 25.4 mm thicknesses. Three complementary methods were used to measure the three orthogonal components of the residual stress in the weld coupons, and fracture tests were conducted on single edge notched bending specimens extracted from different regions of the welds and parent metals. The residual stress measurements showed a maximum value of 450 MPa in longitudinal direction, while it was less than 150 MPa in the other two orthogonal directions, revealing that in our material, and with the chosen weld parameters, the residual stresses were biaxial. The fracture resistance of the weldment and parent material was similar, with material microstructure differences being more significant than the measured residual stresses. The study suggests that 316L electron beam weldments are not susceptible to fracture failure due to their high ductility and ability to relieve residual stresses through gross plasticity. Electron beam welding may therefore be suggested as a reliable manufacturing technology for safety critical 316L components.